Effective teaching of the macro-skills: reflections from Filipino teachers of English. Issue 6 (2nd November 2018) - Mante-Estacio, Ma. Joahna; Nino Valdez, Paolo; Pulido, Dennis
ABSTRACT: The English Language Teacher's ability to examine his/her own practices and beliefs is always an area of language-teaching research worth exploring because the findings have an impact on classroom practice. However, while research on teaching the macro-skills is a rich area in the discipline, teacher beliefs in this aspect remain underexplored especially in developing countries such as the Philippines. This paper examines beliefs of teacher effectiveness in implementing lessons in the macro-skills among ESL teachers in the Philippines. Using data from reflective logs and interviews of 16 teachers of English in the Philippines, data reveal that the main beliefs among teachers center on learner centeredness, instructional skills in teaching the macro-skills and professional development. This paper argues that among the macro-skills, writing and speaking pose challenges in lesson implementation. In addition, the findings suggest that beliefs in effective teaching of the macro-skills are related to learner centeredness, instructional effectiveness and culture contribute to a nuanced account of teacher belief research in English language teaching in the Philippine context.